Layanan Lansia di Panti Sosial Tresna Werdha Kasih Sayang Ibu Batusangkar Sumatera Barat - Suci, Anggi Bima; Tahyudin, Didi; Husin, Azizah (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This study aims to find out the services provided by the Tresna Werdha Kasih Sayang Ibu Social Institution Batusangkar Tanah Datar District West Sumatra Province, to the elderly who are supported. The method used is qualitative with primary and secondary data sources. His research subject was the Head of the Home, two nursing staff and three elderly people who were still able to communicate normally. Data collection techniques are observation, interviews, and documentation. The services provided by the institution to the elderly are good, both from health services, mental and spiritual services, physical services, social and legal services, as well as services for assistive devices. It's just that the problems that arise are in the non-technical factor, that is the excess of health workers, the absence of permanent doctors who are ready if there is a night incident, as well as the lack of cleaning staff.